What they had [videorecording (DVD)] - Chomko, Elizabeth; Swank, Hilary; Shannon, Michael, 1974-; Forster, Robert, 1942-2019- (Universal Pictures Home Entertainment, 2019)
Bridget returns home to Chicago at her brother's urging to deal with her ailing mother and their father's reluctance to let go of their life together.